Karakteristik Kemampuan Berbahasa Anak Tunagrahita dalam Video YouTube “Mengenal Sisi Pendidikan Anak Tunagrahita”: Characteristics of Language Ability of Children with Mental Disabilities in The YouTube Video "Understanding The Educational Side of Children with Mental Disabilities” - Afina Nur Imamah; Ayesha Fazila Febryanti; Kayla Rahmania Azhani; Yoga Rifqi Azizan; Mintowati Mintowati (Transformatika: Jurnal Bahasa, Sastra, dan Pengajarannya, 2026)
This study discusses the characteristics of language abilities of children with intellectual disabilities in the YouTube video “Understanding the Educational Side of Children with Mental Disabilities.” The study aims to describe the forms of language use, expressive and receptive language abilities, and the linguistic characteristics of the children’s utterances in the learning process. This study employed a descriptive qualitative approach. The research data consisted of verbal utterances produced by children with intellectual disabilities in a learning video at a Special School (SLB). The data were collected through observation and note-taking techniques, then analyzed through data reduction, data classification, linguistic analysis, data interpretation, and conclusion drawing. The results showed that the language abilities of children with intellectual disabilities were dominated by the use of single words, short phrases, and simple sentence structures. In the linguistic aspect, limitations were found in phonology, syntax, and lexicon, such as articulation disorders in certain sounds, the use of simple language structures, and limited vocabulary. Nevertheless, the children’s pragmatic abilities showed relatively good development because they were able to understand questions, provide context-appropriate responses, express emotions, and use language as a means of social communication. Thus, the language abilities of children with intellectual disabilities are represented as structurally limited but still function communicatively in social interactions.